Techniques for Advertising Healthy Food in School Settings to Increase Fruit and Vegetable Consumption - Shariwa Oke MS; Marcia Tan PhD (SAGE Publishing, 2022)
Background Childhood obesity rates in Western developed countries are rapidly increasing. While research shows that eating more fruits and vegetables (FV) is a preventive measure, children do not eat adequate amounts of FV. Marketing of high salt, fat, and sugar foods influences children's eating behaviors, decreases FV consumption, and is prevalent in children's surroundings. Garnering the power of ads on children, a potential solution for increasing FV consumption is FV marketing/advertising. Schools can serve as a viable option for testing this advertising because a significant amount of children's time is spent in school settings. However, research surrounding the use of FV advertising in schools is lacking in a consensus on the most effective methodologies. Objective This paper reviewed existing research on FV advertising in schools and proposed directions for future research surrounding methodology and experimental design. Study Design, Setting, Participants PubMed and PsycINFO databases were searched with variations of the terms "vegetable," "marketing," "advertisements," "consumption," and "schools" (eg, "vegetable consumption AND advertisements AND schools". Study inclusion criteria were: conducted in school settings, used FV marketing as primary intervention, and measured change in FV consumption or preference. Measurable Outcome/Analysis This review qualitatively compared the studies' participant demographics, methodologies, and measures of success, and evaluated the studies' strengths and weaknesses. Results Of the 38 articles reviewed, 8 met the inclusion criteria. Five studies examined elementary school populations; 4 were conducted in cafeterias. Major forms of advertising/interventions were print media, video media, and classroom education interventions, of which print media was the most widely used. Three articles utilized change in consumption of FV as a measure of success, while others measured change in preference. All studies reported increased consumption/preference in at least 1 intervention during or immediately after the intervention. However, only 4 studies conducted follow-up testing. Conclusion FV advertisements in schools appear to be effective in increasing FV consumption among children. To develop implementable advertising, future studies should maintain cohesive methodologies by controlling for novelty effects, conducting follow-up testing, and measuring actual FV consumption rather than preference.